Factors Influencing the Quality of Life (Qol) Among Thai Older People in a Rural Area of Thailand - Donnapa Hongthong; Ratana Somrongthong; Paul Ward (Tehran University of Medical Sciences, 2015)
Background: The population prevalence of older people has been growing worldwide. Quality of Life (QoL) among older people is a significant public health concern. Hence, this study aimed to assess level of QoL and factors influencing QoL among rural Thai older people. Methods: The study was undertaken in Phayao Province where is one of the top ten provinces with the highest index of Thai aging. A district in this province was purposively selected to be the study area and the quota-sampling technique was used for sample collection, totally 400 older people participated according to Taro Yamane. The WHOQoL-Old was employed to interview elderly QoL. Multivariate linear regression was performed to determine the factors influencing QoL among the older people. Results: Over two-thirds of older people (68.5%) had QoL at fair level. The vast majority (96%) had high scores for Activity Daily Living (ADL). Approximately one-fifth (20.5%) reported current smoking and 31.7% reported ever drinking during previous year. Following univariate analysis, nine factors - gender, age, education, working, income, present illness, drinking, ADL, and participating in elderly club were identified as being significantly associated with QoL (P <0.05). Multivariate analysis revealed four factors predictive of QoL among elderly: ADL, income, alcohol drinking, and present illness (P < 0.01). Conclusion: Physical function, health status and financial were the predictor of QoL among elderly. Noticeably, drinking was one predictive factor of QoL but only among moderate drinkers. Hence, healthy life style should be considered as key areas in attempts to promote QoL among elderly people.